Secondary syphilis associated crescentic glomerulonephritis: A case report - Marcelo Santos Sampaio; Grigoriy Alexander Shekhtman; Mandana Rastegar; Richard Michael Treger; Glenn Tetsu Nagami; Jonathan Eric Zuckerman (Elsevier, 2021)
Introduction: Syphilis is a sexually transmitted disease caused by the bacterium Treponema Pallidum and has a diverse clinical presentation, including nephropathies, the most common of which is membranous nephropathy. Crescentic glomerulonephritis is not typically considered to be a manifestation of Syphilis associated renal disease. Case presentation: Here we describe an unusual case of crescentic glomerulonephritis associated with secondary syphilis resulting in a rapidly progressing glomerulonephritis presentation requiring hemodialysis. The patient was treated with Penicillin G and intravenous solumedrol. The patient's kidney function recovered and several months after presentation the patient was asymptomatic off hemodialysis with a serum creatinine of 1.54 mg/dL. Discussion/conclusion: Secondary syphilis rarely presents with rapidly progressive glomerulonephritis. This report is only the third such case reported to date of a diffuse necrotizing/crescentic glomerulonephritis resulting from a syphilis infection. As syphilis is on the rise, this report highlights an important differential diagnostic consideration for any necrotizing/crescentic glomerulonephritis.